Measuring what matters? mapping higher education internationalization in the Asia–Pacific. Issue 2 (25th January 2021) - Williams, James H.; Brehm, Will; Kitamura, Yuto
Abstract : Purpose: This paper sought to understand at one time point what was known and not known about the status and use of indicators of internationalization of higher education in Asia–Pacific. More specifically, we identified and mapped publicly available indicators of international of higher education in the region. We examined the ways by which internationalization has been measured and the indicators used, setting up discussion of what may be missing from internationalization efforts. Design/methodology/approach: The primary questions were: (1) What are the current available sources of data in the Asia–Pacific region? (2) How is internationalization measured in publicly available databases and academic materials in Asia–Pacific? To answer these questions, we carried out a structured search of academic and agency literatures. Review of these literatures led us to develop definitions and a classification system by which indicators were classified and examined. Findings: Indicators clustered almost exclusively around measures of student mobility, neglecting a wide range of other possible measures. The authors discuss the implications for internationalization of higher education in the region and draw on existing critical literature to speculate why this might be the case, and what dimensions of internationalization are likely overlooked with such a limited focus. Originality/value: Internationalization of higher education has gained considerable momentum worldwide in recent years, and higher education in the Asia–Pacific region is arguably the world's most dynamic. Despite such dynamism, no research to our knowledge has mapped the way in which internationalization is measured by actors in the region.